Specificity Influences in (1→3)-β-d-Glucan-Supported Diagnosis of Invasive Fungal Disease - Malcolm A. Finkelman (Journal of Fungi, 2020)
(1→3)-β-glucan (BDG) testing as an adjunct in the diagnosis of invasive fungal disease (IFD) has been in use for nearly three decades. While BDG has a very high negative predictive value in this setting, diagnostic false positives may occur, limiting specificity and positive predictive value. Although results may be diagnostically false positive, they are analytically correct, due to the presence of BDG in the circulation. This review surveys the non-IFD causes of elevated circulating BDG. These are in the main, iatrogenic patient contamination through the use of BDG-containing medical devices and parenterally-delivered materials as well as translocation of intestinal luminal BDG due to mucosal barrier injury. Additionally, infection with Nocardia sp. may also contribute to elevated circulating BDG. Knowledge of the factors which may contribute to such non-IFD-related test results can improve the planning and interpretation of BDG assays and permit investigational strategies, such as serial sampling and BDG clearance evaluation, to assess the likelihood of contamination and improve patient care.